Pengaruh Keaktifan Siswa Dan Komunikasi Matematis Terhadap Prestasi Belajar Matematika Siswa - Faridatus Solicha (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2020)
Activity of students while studying in the classroom, both liveliness notes, ask and answer, and also presented the results that have been obtained in working on the teacher as well as good communication skills math will affect the value or the mathematical achievement of every child. The reality in the classroom there are students who are still active under the standard category. While the mathematics communication seen from the test results to the problems given by the researchers. In this study the research method used is quantitative method by using regression and correlation. In this study, a random sampling technique (random) and sample as many as 19 students. Research results obtained show: (1) There is a significant influence on the activity of the student mathematics achievement. From the ANOVA summary table is seen that for a significance level of 5% or 0.05 obtained sig = 0.000 <0.05. Thus, H0 is rejected and H1 accepted, meaning that there is significant influence activity of students towards mathematics achievement. (2) There is a significant effect on the learning achievement of mathematics communication matematika.Dari ANOVA summary table is seen that for a significance level of 5% or 0, 05 obtained sig = 0.005 <0.05. Thus, H0 is rejected and H1 accepted, meaning a significant influence to the mathematical communication mathematics achievement. (3) There is a significant effect of active students and mathematical communication to mathematics achievement. From the summary table SUMMARY seen that for a significance level of 5% or 0.05 obtained sig = 0.000 <0.05. Thus, H0 is rejected and H1 accepted, meaning a significant influence on the activity of mathematical communication siswadan mathematics achievement. So we can conclude there are significant take active students and mathematics communication terhdap mathematics achievement. And advice from researchers for teachers is should provoke students to active learning time in class conducted, and also familiarize students to communicate mathematically up, especially in math. meaning that there is a significant effect on the activity of mathematical communication siswadan mathematics achievement. So we can conclude there are significant take active students and mathematics communication terhdap mathematics achievement. And advice from researchers for teachers is should provoke students to active learning time in class conducted, and also familiarize students to communicate mathematically up, especially in math. meaning that there is a significant effect on the activity of mathematical communication siswadan mathematics achievement. So we can conclude there are significant take active students and mathematics communication terhdap mathematics achievement. And advice from researchers for teachers is should provoke students to active learning time in class conducted, and also familiarize students to communicate mathematically up, especially in math.